2011
DOI: 10.3177/jnsv.57.65
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Visceral Fat Is Positively Associated with Serum ALT and γ-GTP Activities in Healthy and Preclinical Middle-Aged Japanese Men

Abstract: Summary Elevated circulating alanine aminotransferase (ALT) and ␥ -glutamyltransferase ( ␥ -GTP) activities, and the accumulation of fat, particularly visceral fat, in healthy and preclinical subjects reportedly increase the risk for metabolic diseases such as diabetes. In the present study, we examined the associations between these hepatic enzymes and the total visceral and subcutaneous fat area, and for both regions of fat independently, in healthy and preclinical middle-aged Japanese men. We conducted a cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Furthermore, elevated levels of ALAT and γ-GT activities have recently been shown to be positively associated with accumulation of visceral fat ( 12 ) . In the present study, we found that the high-ALA-DAG group non-significantly reduced their circulating concentrations of ALAT, γ-GT and ALP after intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, elevated levels of ALAT and γ-GT activities have recently been shown to be positively associated with accumulation of visceral fat ( 12 ) . In the present study, we found that the high-ALA-DAG group non-significantly reduced their circulating concentrations of ALAT, γ-GT and ALP after intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Also, hepatic accumulation of fat is common in obese individuals and is associated with hepatic dysfunction ( 11 ) . Increased adipose tissue, and in particular visceral adipose tissue, is linked to increased levels of circulating liver function markers, such as alanine aminotransferase (ALAT) and γ-glutamyl transferase (γ-GT) ( 12 – 16 ) .…”
mentioning
confidence: 99%
“…From July 2005 to March 2007, we recruited individuals who attended a health checkup at a local health center in Shizuoka, Japan (Mochizuki et al, 2011;Endoh et al, 2015a;Endoh et al, 2015b). An in-person explanation was provided and written informed consent for participation in the study was obtained from 12,066 subjects.…”
Section: Subjectsmentioning
confidence: 99%
“…, subjects who underwent a health checkup at a local health center in Shizuoka, Japan, were invited to participate in the study (20). A face-to-face explanation was provided and written informed consent for participation in the study was obtained from 12,066 subjects.…”
Section: Subjects From July 2005 To March 2007mentioning
confidence: 99%